2020
DOI: 10.5194/hess-24-3451-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of meteorological-forcing resolution on hydrologic variables

Abstract: Abstract. Projecting the spatiotemporal changes in water resources under a no-analog future climate requires physically based integrated hydrologic models which simulate the transfer of water and energy across the earth's surface. These models show promise in the context of unprecedented climate extremes given their reliance on the underlying physics of the system as opposed to empirical relationships. However, these techniques are plagued by several sources of uncertainty, including the inaccuracy of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…In ecology, flow signatures are used to group watersheds into scale‐independent classes according to their dynamics, before developing within‐class relationships between flow alteration and ecological responses (Kennard, Pusey, et al, 2010; Poff & Ward, 1989). However, signatures can sometimes be sensitive to scale, such as modeled future changes in signatures that depend on climate model scale (Maina, Siirila‐Woodburn, & Vahmani, 2020; Mendoza et al, 2016).…”
Section: Methods In Using Hydrologic Signaturesmentioning
confidence: 99%
“…In ecology, flow signatures are used to group watersheds into scale‐independent classes according to their dynamics, before developing within‐class relationships between flow alteration and ecological responses (Kennard, Pusey, et al, 2010; Poff & Ward, 1989). However, signatures can sometimes be sensitive to scale, such as modeled future changes in signatures that depend on climate model scale (Maina, Siirila‐Woodburn, & Vahmani, 2020; Mendoza et al, 2016).…”
Section: Methods In Using Hydrologic Signaturesmentioning
confidence: 99%
“…For example, the SWE distribution under 400 m and 800 m PRISM resembles more closely with ASO SWE than results under much coarser spatial resolution. Maina et al (2020) also found the SWE distribution to be sensitive to the spatial resolution of meteorological forcing, with the finer resolution being able to accurately reproduce SWE spatial distribution as well as total SWE volume. In addition, a higher spatial resolution of forcing would preserve the spatial heterogeneity of distributed variables better and may provide better estimates of variables at point locations (e.g., SWE at the NRCS's Snowpack Telemetry (SNOTEL) stations and groundwater table at wells).…”
Section: Effects Of Meteorological Forcing Temporal Resolutionmentioning
confidence: 85%
“…It has the flexibility of generating much finer spatial and temporal resolution output while providing all available meteorological forcing. Maina et al (2020) used the nested-domain configuration of WRF to dynamically generate meteorological forcing variables at various spatial resolutions (from 0.5 km to 13.5 km) for use with ParFlow-CLM. Although forcing generated by WRF provides a viable option for meteorological input in the hydrologic model, it requires more effort to simulate the forcing using WRF than directly using the publicly available gridded forcing (e.g., Daymet).…”
Section: Effects Of Meteorological Forcing Temporal Resolutionmentioning
confidence: 99%
“…Simulated key parameters controlling the snow dynamics such as peak snow and timing of snow ablation were also in agreement with remotely sensed data for both dry and wet years. More details about model calibration and validation can be found in previous publications (Maina et al, 2020a, Maina et al, 2020bMaina and SiirilaWoodburn, 2020c). The model has also been successfully used in recent investigations of post-wildfire and climate extremes hydrologic conditions and to assess the role of meteorological forcing scale on simulated watershed dynamics (Maina et al, 2020a, b;Maina and SiirilaWoodburn, 2020c).…”
Section: Integrated Hydrologic Model: Parflow-clmmentioning
confidence: 99%
“…We perform these couplings on spatial and temporal scales relevant for atmosphere-toland, and land-to-subsurface interactions, an important consideration, given the recent work showing the importance of meteorological forcing resolution in representing the hydrologic cycle (Kampenhout et al, 2019;Maina et al, 2020b;Rhoades et al, 2016;Rhoades, Ullrich, Zarzycki, et al, 2018c;Wu et al, 2017). Climate conditions for EoC (2070-2100) and a 30-year historical period are simulated to identify the median, wettest, and driest water year (WY) in each.…”
Section: Introductionmentioning
confidence: 99%